2011
DOI: 10.1097/dcr.0b013e3182271a54
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Modified Estimation of Physiologic Ability and Surgical Stress in Colorectal Carcinoma Surgery

Abstract: Among the models, modified Estimation of Physiologic Ability and Surgical Stress was the most accurate in predicting postoperative mortality in colorectal carcinoma surgery. These findings should be validated in Western populations, because the Japanese population may differ from Western populations in terms of body shape or reserve capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Haga et al, therefore, developed modified E-PASS (mE-PASS) which assess surgical risk according to the type of surgical procedure rather than the concrete factors during the operation. [ 19 ] The mE-PASS showed a similar predicting ability with E-PASS in some researches, [ 12 , 13 ] but it also had limitations in clinical use. In the mE-PASS system, only routine surgical procedure can be assessed, whereas procedures such as emergency surgery or multiple organ resections cannot be assessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Haga et al, therefore, developed modified E-PASS (mE-PASS) which assess surgical risk according to the type of surgical procedure rather than the concrete factors during the operation. [ 19 ] The mE-PASS showed a similar predicting ability with E-PASS in some researches, [ 12 , 13 ] but it also had limitations in clinical use. In the mE-PASS system, only routine surgical procedure can be assessed, whereas procedures such as emergency surgery or multiple organ resections cannot be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Estimation of physiologic ability and surgical stress (E-PASS) system is a more recent predicting system developed by Haga et al [ 10 ] According to his following examination studies, E-PASS was reported to have a good death predicting ability in various surgeries including colorectal cancer surgery. [ 11 13 ]…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, a mortality prediction risk score was developed termed Estimation of Physiological Ability and Surgical Stress (E-PASS) [ 10 ] using parameters to assess the health status of the patient (ASA score, co-morbidities, performance status) and the stress of surgery (blood loss, operation time, open or laparoscopic surgery). E-PASS has been validated for patients undergoing elective general surgery [ 11 , 12 ] and colorectal surgery [ 13 ]. E-PASS has not been validated in a UK-based population.…”
Section: Introductionmentioning
confidence: 99%
“…We recently modified this model, termed mE-PASS, to maintain the discrimination power with a reduced number of variables [8]. We also demonstrated its efficacy in a specialty field of surgery for colorectal carcinoma [9], gastric carcinoma [10], liver carcinoma [11], and choledochocystolithiasis [12].…”
Section: Introductionmentioning
confidence: 99%